PENERAPAN METODE DRILL UNTUK MENINGKATKAN KETERAMPILAN KOLASE DARI BAHAN ALAM SISWA KELAS III SD NEGERI 138 PEKANBARU - Lestari, Indah; Antosa, Zariul; Munjiatun, Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
AbstractThe problem studied in this research is low skills of students in making a collage of natural materials in teaching Arts and Skills. The purpose of this research is to improve the skills of making a collage of natural materials in class III SDN 138 Pekanbaru with the adoption of the drill. This research is a class action consisting of 2 cycles. Based on the assessment skills Intial seen from the data, the average was 54.23 students in the class. After the implementation of the method of cyclus first drill, the average score of students increased to 63.11 and the second cyclus, the average score of students increased to 82.4. Based on the analysis of the above data it can be concluded that the application of the method can improve the skill drill to make a collage of natural materials in class III SDN 138 Pekanbaru.